Timeless Connections: Quantum Entanglement and Spiritual Perspectives on Universal Evolution - Goshu, Belay Sitotaw; Ridwan, Muhammad (Budapest International Research in Exact Sciences (BirEx) Journal, 2024)
This work investigates the relationship between spiritual interconnection and quantum field theory (QFT) by adding a holistic parameter Λ to the potential function V(ϕ, Λ)=0.5m2ϕ2+ΛV0ϕ4. Higher levels of interconnection boost quantum correlations since the study shows that the expected value of spin correlation <S1⋅S2> is directly related to Λ. The enormous influence of non-linear interactions in quantum systems is highlighted by numerical calculations that demonstrate a linear relationship between Ϋ and spin correlation. These results imply that holistic variables can modulate quantum entanglement, giving empirical credence to spiritual beliefs on the unity and oneness of all reality. The ramifications of the discovery extend beyond quantum technologies, where optimizing the entanglement qualities for computing, cryptography, and sensing applications could be achieved by adjusting the holistic parameter. Furthermore, this study promotes an integrated knowledge of the cosmos by bridging the gap between reductionist and holistic scientific paradigms. To gain a deeper understanding of how reality is interconnected, future research should explore the impact of holistic parameters on various quantum domains and promote interdisciplinary cooperation. This all-encompassing method aligns with the metaphysical aspects of life, enhancing both spiritual and scientific knowledge.